“Viver do que se sabe fazer”: memória do trabalho e cotidiano em Santiago do Iguape (1960-1990) - Cruz, Ana Paula Batista da Silva (2014)
The present study is about histories of life, everyday living way and working memory in Santiago do Iguape, a maroon enclave situated in Bahia State’s Reconcavo region, in the lands of Cachoeira’s municipality, between 1960 and 1990’s decades. Living of what one knows how to do: “everyday living way and working memory in Santiago do Iguape, 1960-1990” threw glances at the locality’s inhabitants, seeking to learn their struggles for survival in ways of doing. This research shows that residentshad a close relationship with nature, developing different productive activities, in the midst of the decline of the sugar cane plants environment.Among these activities, men and women saw within fishing, shellfish gathering, plantations, in the weaving of the network, the work at Opalma’s palm oil factory, opportunities for family sustenance, embedded in a tradition of rural riverside-workers, field and sea experiences in Bahia’s concave lands. The research shows the customary uses of lands in Santiago de Iguape rural area, aiming to contribute with its rural enclave’s political struggles understanding, questing maroon land titlings. These individuals’ life historic research, working directly with their personal memories, enabled to uncover the daily life impacted by changes in lifestyle and daily toils amidst the changes experienced in both the Reconcavo of Bahia and in the state capital. The analysis of these memories especially allowed the learning of several meanings of living, giving visibility to the rural population’s know how and how to deal with ways of life in Bahia Reconcavo region.